2021
DOI: 10.3390/cancers13081878
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bacterial and Viral Pathogens in Gastric Carcinogenesis

Abstract: Gastric cancer (GC) is one of the deadliest malignancies worldwide. In contrast to many other tumor types, gastric carcinogenesis is tightly linked to infectious events. Infections with Helicobacter pylori (H. pylori) bacterium and Epstein–Barr virus (EBV) are the two most investigated risk factors for GC. These pathogens infect more than half of the world’s population. Fortunately, only a small fraction of infected individuals develops GC, suggesting high complexity of tumorigenic processes in the human stoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 233 publications
(165 reference statements)
1
23
0
Order By: Relevance
“…Gastric carcinogenesis associated with H . pylori infection is determined by complex and still not well understood interactions between bacteria and human cells [ 2 ]. Previous studies have shown that one of the bacterial virulence determinants closely linked to tumorigenesis is CagA protein [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric carcinogenesis associated with H . pylori infection is determined by complex and still not well understood interactions between bacteria and human cells [ 2 ]. Previous studies have shown that one of the bacterial virulence determinants closely linked to tumorigenesis is CagA protein [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…After translocation, CagA is phosphorylated by host tyrosine kinases at the EPIYA (Glu-Pro-Ile-Tyr-Ala) repeatable motifs located at the carboxy-terminal end of the CagA molecule. CagA is responsible for alteration of multiple signaling pathways and aberrant activation of various oncogenic proteins such as Ras, β-catenin, PI3K, and others [ 2 ]. The full spectrum of host interacting partners of CagA protein still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Neoplastic cells are characterized by reduced growth control, invasiveness to the tissues in which they occur, and the ability to spread. More and more often, attention is paid to the contribution to neoplasms formation by broadly understood infectious agents ( Fol and Jachowicz 2016 ; Masrour-Roudsari and Ebrahimpour 2017 ; Palrasu et al 2021 ). It is estimated that they could cause up to 20% of cancers.…”
mentioning
confidence: 99%
“…Stomach cancer incidences and mortality vary greatly depending on environmental factors such as diet, alcohol consumption, smoking, cancer stage at diagnosis, and genetic burden. Helicobacter pylori and the Epstein-Barr virus are mentioned as significant risk factors for developing gastric cancer ( Fasciana et al 2019a ; Machlowska et al 2020 ; Sexton et al 2020 ; Palrasu et al 2021 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation